Multifunctional magnetic-responsive hydrogels to engineer tendon-to-bone interface - Silva, E. D. (2018)
Photocrosslinkable magnetic hydrogels are attracting great interest for tissue engineering strategies due to their versatility and multifunctionality, including their remote controllability ex vivo, thus enabling engineering complex tissue interfaces. This study reports the development of a photocrosslinkable magnetic responsive hydrogel made of methacrylated chondroitin sulfate (MA-CS) enriched with platelet lysate (PL) with tunable features, envisioning their application in tendon-to-bone interface. MA-CS coated iron-based magnetic nanoparticles were incorporated to provide magnetic responsiveness to the hydrogel. Osteogenically differentiated adipose-derived stem cells and/or tendon-derived cells were encapsulated within the hydrogel, proliferating and expressing bone- and tendon-related markers. External magnetic field (EMF) application modulated the swelling, degradation and release of PL-derived growth factors, and impacted both cell morphology and the expression and synthesis of tendon- and bone-like matrix with a more evident effect in co-cultures. Overall, the developed magnetic responsive hydrogel represents a potential cell carrier system for interfacial tissue engineering with EMF-controlled properties.